Diversity of fungi in mangrove ecosystem - K.M. Khaleel, V. V Gilna*, (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present study was taken with an objective to asses the occurrence of fungi on leaves, bark and pneumatophores from the selected mangroves, fungi from soil and water was also recorded and physicochemical parameters of soil and water were noted. Maximum number of fungi was isolated from soil. Pneumatophores of Avicennia marina showed more fungal count than leaf and bark of other mangroves.Aspergillus spp were found to be dominant among the various fungal species isolated from the mangrove ecosystem.